ANALISIS SIFAT FISIK TANAH PADA BEBERAPA PENGGUNAN LAHAN DI DAERAH ALIRAN SUNGAI TAWAELI - Haryati, Siti; Hasanah, Uswah; Pagiu, Salapu (AGROTEKBIS, 2019)
This research cal to determine soil physical properties on some land uses in the watershed (DAS) Tawaeli Palu City. Research carried out in watersheds the Tawaeli 8 units of dryland farming, shrubs, primary forestwith three classes of slopes included0-8%, 8-15% and 15-25%. soil analysis is done in soil science laboratory, Faculty of Agriculture, tadulako university. This research was conducted in December 2017 until April 2018. Determination of soil sample Location taken for analyse laboratory determined in the Purposive Sampling as much 8 sample poin. Research results show the physical properties DAS Tawaeli units of dryland farming, shrubs, primary forestwith each slope different, have diverse soil physical properties found in some of the land uses studied in DAS tawaeli. The soil fraction is dominated by sand and dust with clay texture class, dusty clay and sand clay. have low to very high organic materials, hydraulic conductivitymoderate to moderately fast, weight volume medium to heavy, porosity is very bad to bad, field capacity and low to high saturated water content, limits of liquid and medium to high plastic.